2019
DOI: 10.1308/rcsann.2018.0186
|View full text |Cite
|
Sign up to set email alerts
|

Image guided surgery for removal of deep foreign bodies and soft tissue tumours using portable ultrasonography

Abstract: This technique can make the lesions visible by patent blue dye and make the surgery more efficient and accurate. Our experience demonstrates the advantages of the hybrid technique are; A periareolar incision results in a better cosmetic result and does not interfere with subsequent procedures for cancer patients. It is less traumatic with less postoperative pain. In our study, post-procedural specimen mammography showed that the microcalcification is adequately probed and no re-excision is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…5,11,13,14 Common applications for portable ultrasound include evaluation for cardiac or abdominal abnormality. 5,14 The use of portable ultrasound in the musculoskeletal system has been described for foreign body removal 7,9 and rib fracture assessment. 12 One study evaluated 10 shoulders and concluded that abnormality could be identified 10 ; however, a comprehensive evaluation of routine musculoskeletal applications has not been previously assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,11,13,14 Common applications for portable ultrasound include evaluation for cardiac or abdominal abnormality. 5,14 The use of portable ultrasound in the musculoskeletal system has been described for foreign body removal 7,9 and rib fracture assessment. 12 One study evaluated 10 shoulders and concluded that abnormality could be identified 10 ; however, a comprehensive evaluation of routine musculoskeletal applications has not been previously assessed.…”
Section: Discussionmentioning
confidence: 99%
“…4 Such equipment has been used in several applications, such as trauma, cardiorespiratory assessment, and invasive procedures 4 ; however, the effectiveness of portable ultrasound in evaluation of the musculoskeletal system has not been fully assessed. 7,9,10,12 Thus, the purpose of this study was to evaluate the use of a portable hand-held ultrasound device in the evaluation of the musculoskeletal system compared with conventional cart-based ultrasound. The hypothesis was that portable hand-held ultrasound would be as effective as conventional cart-based ultrasound.…”
mentioning
confidence: 99%